Pemberdayaan Masyarakat Dalam Pengelolaan Sampah Skala Rumah Tangga untuk Mewujudkan Kabupaten Banyuwangi Sehat - Nur Anim Jauhariyah; Mahmudah Mahmudah; Pipit Hariyono; Ana Aniati (LOYALITAS: Jurnal Pengabdian Kepada Masyarakat, 2022)
Changes in people's behavior in waste management are very important, as a solution to the waste problems that have occurred so far. The purpose of this service is to provide an overview of the education community in managing household-scale waste. This dedication approach uses Participatory Action Research (PAR). The results of the service show that so far the handling of household waste in Alasmalang Village, Singojuruh District, is still being burned and thrown into the river. This can become a public health problem, in addition to the problem of flooding which will threaten at any time. In supporting the Healthy Banyuwangi Regency, it is necessary to educate and assist in separating and sorting waste from households on an ongoing basis.